Institutional Performance of Dairy Farmers and The Impacts on Resources - Amam Amam; Mochammad Wildan Jadmiko; Pradiptya Ayu Harsita (Universitas Muhammadiyah Yogyakarta, 2020)
Farmers institution is an organization that allows farmers to carry out farm agribusiness activities, from upstream (input) to downstream (processing and marketing), and connect with stakeholders. This study aims to investigate the institutional performance of dairy farmers and analyze its impact on resources. The research was conducted on May to September 2019 in Pujon sub-district, Malang district, East Java. The respondents were the 174 farmers registered as the member of Tirtasari Kresna Gemilang Joint Business Group (KUB). The data collection utilized Focus Group Discussion (FGD), observation, and survey. The survey was held through interviews and questionnaires with +1 to +5 Likert scale. The variables of this study were institutional performance (X), economic resources (Y), environmental resources (Y2), and social resources (Y3). The data was analyzed using the PLS (Partial Least Square) method. The result of the study shows that institutional performance affects economic, environmental, and social resources 31.3%, 21.9%, and 45.6%, respectively. This study concluded that the institutional performance of dairy farmers positively and significantly influences the economic and social resources, but insignificantly influences environmental resources.